2004
DOI: 10.2113/107.1-2.301
|View full text |Cite
|
Sign up to set email alerts
|

Preferential distribution along transcontinental corridors of kimberlites and related rocks of Southern Africa

Abstract: Regional and local structural controls on the emplacement of 1326 Southern African kimberlites and related rocks (kimberlites sensu lato, 11% of which are dated) are analysed using a framework of lineaments defined by combining geology, aeromagnetics, gravity and geomorphological data. Spatial analysis of occurrences within clusters of kimberlites less than 100km across resolves variable trends, depending on the age and position of the cluster; but on a regional scale the distribution of these clusters is stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 67 publications
2
85
0
Order By: Relevance
“…The last two best fit the spatial arrangement and age data of the kimberlites (Jelsma et al, 2004). A study of more than 1300 kimberlite occurrences in Southern Africa in relation to regional geological and geophysical data shows that there is a statistical probabability of a pronounced structural control on the location of these rocks (Jelsma et al, 2004, Basson and.…”
Section: Punctuated Kimberlitic Magmatism Across Southern Africamentioning
confidence: 90%
See 3 more Smart Citations
“…The last two best fit the spatial arrangement and age data of the kimberlites (Jelsma et al, 2004). A study of more than 1300 kimberlite occurrences in Southern Africa in relation to regional geological and geophysical data shows that there is a statistical probabability of a pronounced structural control on the location of these rocks (Jelsma et al, 2004, Basson and.…”
Section: Punctuated Kimberlitic Magmatism Across Southern Africamentioning
confidence: 90%
“…This eruption frequency is clearly reflected in a dense regional distribution of kimberlites, carbonatites and other and related rocks across southern African (Figure 7, Skinner et al, 1992;Jelsma et al, 2004). The spatial and temporal distribution of these rocks has frequently been related to: 1. mantle plumes, and hot spots; 2. rifting of continents; 3. major faults or basement trends related to oceanic fracture zones; 4. temporal variations in deviatoric stresses related to changes in the motion vector of the African plate during the Cretaceous.…”
Section: Punctuated Kimberlitic Magmatism Across Southern Africamentioning
confidence: 94%
See 2 more Smart Citations
“…For example, Cullen (1958) concluded that northwesterly trending faulting accompanied folding of Transvaal Supergroup strata prior to emplacement of the MFC. The sub-continental trend of kimberlites in the Kaapvaal Craton is northeast to southwest (Jelsma et al, 2004) although the kimberlite fields in southern Botswana (Jwaneng and Kokong, shown on Figure 3) are also aligned as an east to west trending belt. However, northwest to southeast trending faults locally control the emplacement of individual kimberlites in southern Botswana.…”
Section: Geological Setting Of the Mfc In Botswanamentioning
confidence: 98%